Outcomes of Patients Treated in the UK Proton Overseas Programme: Non-central Nervous System Group. Issue 5 (May 2023) - Hwang, E.; Gaito, S.; France, A.; Crellin, A.M.; Thwaites, D.I.; Ahern, V.; Indelicato, D.; Timmermann, B.; Smith, E.
Abstract: Aims: The UK Proton Overseas Programme (POP) was launched in 2008. The Proton Clinical Outcomes Unit (PCOU) warehouses a centralised registry for collection, curation and analysis of all outcomes data for all National Health Service-funded UK patients referred and treated abroad with proton beam therapy (PBT) via the POP. Outcomes are reported and analysed here for patients diagnosed with non-central nervous system tumours treated from 2008 to September 2020 via the POP. Materials and methods: All non-central nervous system tumour files for treatments as of 30 September 2020 were interrogated for follow-up information, and type (following CTCAE v4) and time of onset of any late (>90 days post-PBT completion) grade 3–5 toxicities. Results: Four hundred and ninety-five patients were analysed. The median follow-up was 2.1 years (0–9.3 years). The median age was 11 years (0–69 years). 70.3% of patients were paediatric (<16 years). Rhabdomyosarcoma (RMS) and Ewing sarcoma were the most common diagnoses (42.6% and 34.1%). 51.3% of treated patients were for head and neck (H&N) tumours. At last known follow-up, 86.1% of all patients were alive, with a 2-year survival rate of 88.3% and 2-year local control of 90.3%. Mortality and local control were worse for adults (≥25 years) than for the younger groups. The grade 3 toxicity rate was 12.6%, with a median onset of 2.3 years. Most were in the H&N region in paediatric patients with RMS. Cataracts (30.5%) were the most common, then musculoskeletal deformity (10.1%) and premature menopause (10.1%). Three paediatric patients (1–3 years at treatment) experienced secondary malignancy. Seven grade 4 toxicities occurred (1.6%), all in the H&N region and most in paediatric patients with RMS. Six related to eyes (cataracts, retinopathy, scleral disorder) or ears (hearing impairment). Conclusions: This study is the largest to date for RMS and Ewing sarcoma, undergoing multimodality therapy including PBT. It demonstrates good local control, survival and acceptable toxicity rates. Highlights: Clinical outcomes data collection supports evaluation of proton beam therapy. Largest evaluation of rhabdomyosarcoma and Ewing sarcoma undergoing proton therapy. Comparable tumour and toxicity outcomes despite challenges of global coordination.